Пошук лабораторних критеріїв добору оптимального цукрознижувального препарату для лікування хворих на ЦД-2 за даними перехресного дослідження - Кіхтяк, О. П. (Clinical Endocrinology and Endocrine Surgery, 2010)
Crossover study was conducted in order to discover optimal laboratory criteria for pharmacotherapy of type 2 diabetes mellitus. A list of laboratory tests was established showing much more opportunities in the treatment of type 2 diabetic patients.